Costa Rica : Balance of Payments and International Investment Position Statistics (October 13-23, 2014). (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the recommendations made by the IMF missions on the balance of payments and international investment position dynamics in Costa Rica. In view of the results of the economic survey, the mission recommended that the Central Bank of Costa Rica (BCCR), in cooperation with the Ministry of Finance, follow up with respondents to raise awareness of the importance of reporting transactions by residency. Regarding the work on secondary income, the mission observed that the BCCR has a reliable estimate of income of seasonal and border workers in Costa Rica. It is expected that the BCCR will be able to collect information on pensions received by foreign residents who retire in Costa Rica.